Analytical Method for Evaluation of Coupled Responses of a Multidirectionally Loaded Pile-Raft Foundation Induced by Tunnelling in Layered Soils. (11th June 2015) - Mu, Linlong; Huang, Maosong
Abstract : The tunnelling effect on a pile-raft foundation is usually studied in either the horizontal or vertical direction separately, while, in practice, the responses of a pile-raft foundation induced by tunnelling in the horizontal and vertical directions occur simultaneously. Typically, a pile-raft foundation is usually loaded by vertical and horizontal loads and moments when a tunnel is constructed. Since little effort has been conducted to evaluate the coupled responses of multidirectionally loaded pile-raft foundations subjected to tunnelling, a modified two-stage method is proposed in this paper to evaluate the coupled responses of a multidirectionally loaded pile-raft foundation in layered soil. After careful verification of the method, a parametric study was carried out to evaluate whether it is necessary to consider the influences of tunnelling on a loaded pile-raft foundation from the design stages. Our study showed that it is more necessary to consider the influence of tunnelling on a pile-raft foundation when the working load on the pile-raft foundation is small. When there was only a vertical load working on the raft, the horizontal deformation and the rotation of the raft, as well as any horizontal deformation and moment along the piles, were controlled by tunnelling.